1999
DOI: 10.1177/03635465990270060601
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic-Androgenic Steroid Administration Causes Hypertrophy of Immobilized and Nonimmobilized Skeletal Muscle in a Sedentary Rabbit Model

Abstract: Although the use of anabolic agents in athletics has generated extensive publicity and controversy, the potential therapeutic benefits of these drugs have not been fully investigated. This randomized, blinded experimental study investigated whether short-term administration of an anabolic-androgenic steroid can limit immobilization-induced muscle atrophy in a rabbit model. We casted one hindlimb each in 48 New Zealand White rabbits and randomly assigned the rabbits to two groups. The treated group received wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
30
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 58 publications
4
30
1
1
Order By: Relevance
“…11 Although we did not evaluate nandrolone levels, we did confirm that the osmotic pump delivery system, which is well validated and considered reliable, 55 did successfully deliver its contents. Likewise, our treatment period of 4 weeks was within the range of other studies (2-8 weeks, 54 5-6 weeks, 10 30 days, 18 28 days, 59 14 days, , although still on the conservative side. Salmons, in particular, reported positive effects of anabolic steroids at 12 weeks but not at 4 weeks.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…11 Although we did not evaluate nandrolone levels, we did confirm that the osmotic pump delivery system, which is well validated and considered reliable, 55 did successfully deliver its contents. Likewise, our treatment period of 4 weeks was within the range of other studies (2-8 weeks, 54 5-6 weeks, 10 30 days, 18 28 days, 59 14 days, , although still on the conservative side. Salmons, in particular, reported positive effects of anabolic steroids at 12 weeks but not at 4 weeks.…”
Section: Discussionsupporting
confidence: 80%
“…Salmons demonstrated improved size and strength in the tibialis anterior muscle of female rabbits following 12 weeks of anabolic steroid administration. 45 Taylor et al found a definite anabolic response in a sedentary rabbit model treated with nandrolone decanoate, 54 and Zhao et al found that nandrolone significantly reduced chronic denervation atrophy (but not acute atrophy) in rats when administered 28 days after nerve transection. 59 In certain types of atrophy, including disuse, HIV infection, and sarcopenia, anabolic steroids have been shown to have a positive effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that testosterone or nandrolone reduced muscle atrophy caused by a lack of weight-bearing or immobilization (Taylor et al, 1999;Wimalawansa et al, 1999). In muscle paralyzed by nerve transection, nandrolone slowed atrophy and reduced expression of MAFbx, MuRF1, and FOXO1 (Qin et al, 2010b).…”
mentioning
confidence: 99%
“…Administration of testosterone promotes the differentiation of mesenchymal stem cells into the myogenic lineage (22). Testosterone is able to increase skeletal muscle mass and strength in elderly men and in many conditions resulting in muscle atrophy, such as cancer and burn-induced cachexia (23), microgravity (24), immobilization (25), and spinal cord injury (26). The precise mechanisms underlying these actions of androgens, however, are poorly understood.…”
mentioning
confidence: 99%